Sunshine - Bauer, Marion Dane (Candlewick Press, 2021)
For most of Ben's life, he has been a kid without a mom. He has his dad, who knows Ben doesn't like oatmeal and always hugs Ben before bed. And he has Sunshine, his loyal little dog, who is never far from his side. But his mom, who left when he was young, has just been a story, faint in his memory. Now he's about to spend a whole week with her on her remote island in the middle of the northern Minnesota wilderness. Though he's nervous about bears and outhouses and what his mom will think of Sunshine, Ben has a plan. When a fire threatens his mom's island, Ben finally realizes everything he's been trying to forget and learns how to forgive his mom - and himself.